For I have sinned: the rise and fall of Catholic confession in America - O'Toole, James M. (Harvard University Press, 2025)
"The history of US Catholicism is the history of confession. For I Have Sinned charts the rise of confession as the defining ritual of American Catholic piety and identity-and its fall, as clergy sex-abuse scandals and the cultural shifts of the 1970s decimated interest in a practice that, today, is alien even to most faithful believers."--